Laboratory equipment 1995/96. (Siber Hegner : Heraeus, 1996)
Contents of this book include: Heating and drying ovens; Vacuum heating and drying ovens; High temperature furnaces; Centrifuges; Incubators; Biohazard, safety and clean room cabinets; Steriliser; Ultra low temperature freezers;...
Keywords: Laboratory; Laboratory equipment